MAIN OUTCOMES OF DEMOGRAPHIC PROCESSES, CURRENT TRENDS AND ISSUES IN THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
Demographic processes have both direct and indirect impacts on the socio-economic development of countries, acting as one of the key factors for sustainable economic growth. In Armenia, changes in population size, reproduction rates, the established gender and age structure, migration processes, and other factors have significantly influenced the country's economic development both during the Soviet period and in the years of independence. The collapse of the USSR, economic crises, geopolitical instability in the region, and other circumstances have led to the formation of a tense demographic situation in Armenia. The article analyzes the main results of existing demographic processes in Armenia, their geographical picture. The problems associated with them are identified and ways to solve them are indicated.
Keywords: Republic of Armenia; demographic processes; reproduction rates; emigration; migration processes; birth rate; mortality rate; main outcomes